Conservation-restauration de l’œuvre d'un artiste vivant - Julie Chanut (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article presents the various phases of a spanish contemporary sculpture's restoration. The goal of the methodology used during the piece documentation was to produce a treatment proposal which fitted the piece's characteristics : its comtemporary nature which brought some intellectual property issues, the originality of the artistic approach, the building process, the material history.